Using cocreated visually informed community mental health education in low‐ and middle‐income countries: A case study of youth substance misuse in Assam, India - Raginie Duara; Diptarup Chowdhury; Ratul Dey; Sangeeta Goswami; Anna Madill (Wiley, 2022)
Abstract Introduction Our aim is to evaluate the visually informed community mental health education materials cocreated in our research on youth substance misuse in Assam, India, and to reflect on what we might learn for similar initiatives in low‐ and middle‐income countries. Methods Materials consist of: (i) images participants brought to the interview; (ii) 30 posters cocreated by participants to convey key messages from their interview; (iii) six short films on the implications of addiction, and (iv) an animation of our Pathways to Recovery model. We also created a community education package that incorporated these materials. We analyse feedback from three groups of events and a social media campaign, which drew variably across our materials and engaged a range of audiences. Results Outcomes indicate the cocreation process and focus on the visual was successful in promoting young people's voice, increasing awareness and has potential for stigma reduction. Our educational package was deemed useful in increasing awareness and has potential for prevention and treatment. Conclusions Our case study offers insights into community mental health education in low‐ and middle‐income countries, confirming the importance of cocreation, the usefulness of visual materials and the potential of social media campaigns while acknowledging the importance of local context in health messaging, particularly for stigmatized topics. Patient or Public Contribution Service users were involved in the cocreation of the materials evaluated in this study and contributed as presenters in one of the events reported. Members of the public took part in events in which the materials were shared and provided us with the feedback analysed in this article.